Chapter 7 : The Removal, Reconstruction And Conservation Of The Gua Gunung Runtuh Skeleton: A Practical Guide. - Chia, Stephen, Ming Soon; Sam, Teng Wah (Department of Museums And Antiquity Malaysia, 1994)

(untitled)
Bone consists of collagen, a proteinous (organic) substance, and a mineral, principally a form of calcium phosphate, called apatite, together with water. The bones in a body have different functions and this difference is reflected in the degree of mineralisation.